THE INFLUENCE OF FIRM SIZE AND CAPITAL STRUCTURE ON FINANCIAL PERFORMANCE IN THE ASEAN MANUFACTURING SECTOR - Gressieni Evelyn; Eduard Ary Binsar Naibaho (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study examines the impact of firm size and capital structure on the financial performance of ASEAN manufacturing companies during the 2014-2023 period, considering the influence of the COVID-19 pandemic. The pandemic triggered a global economic crisis, disrupting corporate financial stability. Total assets and revenue measure firm size, while capital structure is represented by the debt-to-asset ratio (DAR) and debt-to-equity ratio (DER). Financial performance is assessed using return on assets (ROA), and Tobin's Q. Data from 767 companies was collected through purposive sampling and analyzed using a fixed-effects panel data model. The results reveal that total assets have a significant positive impact on ROA but a negative impact on Tobin's Q. Total revenue significantly positively affects both ROA and Tobin's Q. DAR has a significant negative impact on ROA, while DER shows a significant negative effect on Tobin's Q. These findings provide insights for company management in formulating financial strategies and for investors in evaluating investment potential based on firm size and capital structure.